1443 Relation of Birth Weight and Infant Growth With Body Size, Body Composition and Fat Distribution at Age 5–6 Years. (October 2012) - Beer, M De; Eijsden, M Van; Vrijkotte, T; Fall, C; Osmond, C; Gemke, R
Abstract : Background and Aims: In a prospective cohort study (the ABCD study), we investigated the association of early growth with (precursors of) childhood obesity. Methods: Our study was based on 2, 338 term born children with on average 7 measures of growth (weight and length) from birth to age 12 months. We used conditional weight, a residual of current weight regressed on prior weights, to represent deviations from expected weight gain from 0 to 1, 1 to 3, 3 to 6, and 6 to 12 months. The same method was applied for conditional length and body mass index. Relations of these measures with height, body mass index, fat mass (adjusted for height and fat free mass) and waist-to-height ratio (WHtR) at age 5–6 were explored using linear regression analysis. Results: Higher birth weight, weigh conditionals and bmi conditionals for all periods in infancy (expressing faster growth) were associated with increased height, body mass index, fat mass and WHtR. Furthermore, although higher length conditionals after 3 months were associated with higher childhood bmi, no association was found with fat mass. Higher length conditionals were associated with lower WHtR. Conclusions: Faster prenatal growth and subsequent faster infant weight- and bmi gain were associated with greater childhood body size, more fat tissue mass and more central adipose distribution. Conversely, although rapid length gain after 3 months was associated with greater childhood body size, this was not accompanied by more fat tissue mass, yet with less central adipose distribution.